Experimental and modeling analysis on thermoelectric heat recovery to maximize the performance of next-generation diesel engines dedicated for future electrified powertrains. (25th January 2023) - Sok, Ratnak; Kusaka, Jin
Highlights: A fast predictive thermoelectric generator (TEG) model is developed and validated. A 4-cylinder 2.2 L diesel engine model with TEG is developed and calibrated. The effective power of 1.1 kW is generated from a 3-layer TEG (1.5 × A4 size). Brake thermal efficiency of 49.9 % is demonstrated in the next-generation engine. The TEG system improves the engine brake thermal efficiency by 1.1 %. Abstract: Thermoelectric generators (TEG) can recover significant energy loss from exhaust heat and improve brake thermal efficiency (BTE) of internal combustion engine (ICE) vehicles. However, its utilization is restricted due to increased pump losses when it is integrated with ICEs. This work uses a model-based design approach to maximize the performances of a next-generation, production-intent 2.2 L diesel engine dedicated to future electrified powertrains via TEG heat recovery. To take full advantage of TEG in the engine, a thermoelectric module (TEM) arrangement in TEG must be optimized, accounting for a tradeoff between increased pump loss and TEG effective power. Firstly, a high-fidelity 1D TEG model is developed, and a novel model calibration method is proposed by using simplified user-defined functions of heat transfer and flow friction factors. Measured thermal performances of the TEG heat exchanger are reproduced under various fin pitches, Reynolds numbers, and inlet gas conditions. The TEG model is integrated with the well-calibrated engine to maximize its BTE and power. Under the most efficient condition (peak BTE at 2250 RPM, 60% load), BTE = 48.7% and 52.1 kW brake power are obtained under the baseline case without TEG. An optimal 9 × 10 TEM arrangement generates a 1.1 kW effective power from the 3-layer TEG model (1.5 × A4 paper size, 150 mm height, 36 kg weight). Finally, a 1.1% BTE improvement is obtained without power loss in the next-generation, highly efficient, hybridized diesel engine.